Strategi pengembangan ternak Sapi Potong di Kabupaten Pegunungan Arfak, Provinsi Papua Barat - Jan Pieter Rumpaidus; Mohamad Jen Wajo; Stepanus Pakage (Cassowary, 2020)
Arfak Mountains Regency has potential resources for agriculture, plantations, livestock, fisheries and forestry. Arfak Mountains Regency is very potential for the development of beef cattle, but many obstacles are faced. So it is necessary to do research to find out the strengths, weaknesses, opportunities and threats or strategies for developing beef cattle in the Arfak Mountains District, West Papua Province. This study aims to identify the factors that influence the development of beef cattle and develop suitable alternative strategies to be applied in the development of beef cattle in the Arfak Mountains District. The alternative strategy that can be done is to strengthen capital in order to compete, expand the market share of beef cattle and improve the quality of beef cattle products.